Prediction of gymnastics physical profile through an international program evaluation in women artistic gymnastics - Nassib, S. H.; Mkaouer, B.; Riahi, S. H.; Wali, S. M.; Nassib, S. (The Journal of Strength and Conditioning Research, 2020)
The purpose of this study was to investigate the most appropriate aptitudes for top-level sporting results to identify physical profile of talent identified women's artistic gymnastics (WAG). Forty-eight women's artistic gymnasts in the provincial team (age 11.12 ± 1.22 years; height 1.35 ± 0.04 m; body mass 28.5 ± 4.04 kg) voluntarily participated in this study. Anthropometrics measures and the WAG battery physical tests were used to ensure a systematic approach for the WAG development worldwide. The present findings revealed that the strength (static strength, speed strength, and endurance strength), power and flexibility seem to be important and essential for good performance. Another characteristic that emerged from the results of the physical domain is coordination. This motor skill may seem relevant to gymnastics, they are applicable to the gymnasts' ability to perform all apparatus and more generally they relate to the ability to accurately perform whole-body skills supported by the leg on the floor, balance beam, and vault. Therefore, athletic performance can be boosted using combination of several characteristics that seems to be important for an elite gymnast. This reinforcing the view that systematic approach for the development and mufti-dimensional profile seems promising.